Study on the Types, and Metallogenic and Diagenetic Environment of Tourmaline from the Zhongzuo Pegmatite Veins in Quyang County, Hebei Province - HOU Jiang-long; WANG Deng-hong; WANG Cheng-hui; HUANG Fan; LI Jian-kang; CHEN Zhen-yu (Yankuang ceshi, 2017)
Tourmaline is an efficient tracer during diagenesis and metallogenesis. Chemical composition of tourmaline can not only be used to give information about environment of diagenesis and metallogenesis, but can also be useful in prospecting. Prospecting work of pegmatite-type rare metal deposits in Southern and Western China has seen a big breakthrough, however, there has been no obvious advance in prospecting in Northern China. Therefore, it is necessary to carry out systematical and detailed prospecting work. There are a lot of grey black idiomorphic tourmalines in pegmatite veins in Quyang County, Hebei Province, which makes it suitable for carrying out systematical mineralogy research. Samples based on detailed field work were systematically collected and are described in this paper. Microscopic identification, Powder X-ray Diffraction and Electron Microprobe were used to determine the chemical composition of tourmaline, in order to investigate the types, and diagenetic and metallogenic environment of tourmaline. Electronic Probe and Powder X-ray Diffraction show that tourmaline in Zhongzuo pegmatite belongs to dravite but is close to that of schorl. The Ca-Fe-Mg ternary diagram indicates that the diagenetic environment is poor Ca metamorphic pelite, metamorphic arenite and quartz-tourmaline rock. The chemical composition of tourmaline is closely related to the types of surrounding rock. The dravite in pegmatite veins was formed by assimilation blending between magmatic melt and surrounding rock at a temperature of 700-600℃ where Mg and Fe in surrounding rock provide the necessary sources for the formation of tourmaline. The systematical study of chemical composition of tourmaline in Zhongzuo pegmatite veins provides fundamental geological data and a prospecting direction for pegmatite-type deposits.